2018
DOI: 10.1111/tid.12894
|View full text |Cite
|
Sign up to set email alerts
|

Sexual acquisition of HIV infection after solid organ transplantation: Late presentation and potentially fatal complications

Abstract: Sexual acquisition of HIV infection after SOT represents a difficult challenge, as it may occur in any kind of transplant and at any time. The course of infection resembles that of the general population, with life-threatening infectious complications, but good response to ART. Assessment of lifestyle and risk behavior is paramount, as indications may be not disclosed without direct questioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…No new cases of HIV were detected in our cohort, and only three patients with HIV infection received a kidney transplant during the study period, none of which were found to have STIs after transplantation. The incidence of new‐onset HIV after transplantation has been rare also in other studies 18 …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…No new cases of HIV were detected in our cohort, and only three patients with HIV infection received a kidney transplant during the study period, none of which were found to have STIs after transplantation. The incidence of new‐onset HIV after transplantation has been rare also in other studies 18 …”
Section: Discussionmentioning
confidence: 80%
“…The incidence of new-onset HIV after transplantation has been rare also in other studies. 18 Our study has some additional limitations of note. Despite including a relatively large cohort of kidney transplant patients, the number of STI cases diagnosed within our cohort remained small, and multivariable models for risk factors for STIs were not assessed as feasible or reliable, and annual incidence of STIs could not be calculated.…”
Section: Discussionmentioning
confidence: 90%
“…This case highlights the diagnostic challenges of post-transplantation HIV infection with a probable sexual acquisition. This issue is not well described in the literature, only one case series being available from our research [3]. Even though the benefits of transplantation in HIV infected patients has been well known for years, Fig 2. CEUS enhancement in the cortico-medullar (a), early pyelographic (b), and late pyelographic (g) phases show a quick cortical contrast uptake and quick cortical wash-out.…”
Section: Discussionmentioning
confidence: 92%
“…Although the acquisition of HIV through sexual practices in a SOT recipient may be rare, it is not impossible. Fortunately, SOT recipients who acquire HIV can have a good response to antiretroviral therapy 48 …”
Section: Human Immunodeficiency Virus/acquired Immunodeficiency Virusmentioning
confidence: 99%